(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Some of the difficulties encountered in the work of education and upbringing of teenage students arise from insufficient knowledge or denial of mental development and characteristics of children of this age. This article provides information about the characteristics of psychological changes in children during adolescence.